2021
DOI: 10.7150/jca.60737
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA NRON promotes Tumor Proliferation by regulating ALKBH5 and Nanog in Gastric Cancer

Abstract: Long non-coding RNAs (lncRNAs) act as tumor suppressors or oncogenes in tumor development and progression. In this study, we explored the expression and biological role of lncRNA NRON in gastric cancer (GC). We observed that lncNRON was upregulated in GC tissues and cell lines, and high lncNRON expression was associated with malignant features and poor prognosis in GC patients. LncNRON was found to promote the proliferation and tumorigenicity of GC cells. Mechanistically, lncNRON exerted its oncogenic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…According to our RACE results, which showed that NRON was 2,730 nt in both MCF7 (p53 wild‐type cell) and BT474 (p53 mutant cell), we overexpressed the 2,730 nt NRON and found that it promoted breast cancer cell growth in vitro and in vivo . There are also studies supported our observations that NRON increased tumor cell growth, such as in bladder cancer and gastric Cancer (Xiong et al , 2020; Wang et al , 2021), as well as NRON was highly expressed in esophageal squamous cell carcinomas and inhibited cisplatin‐induced cell apoptosis (Liu et al , 2022).…”
Section: Discussionsupporting
confidence: 81%
“…According to our RACE results, which showed that NRON was 2,730 nt in both MCF7 (p53 wild‐type cell) and BT474 (p53 mutant cell), we overexpressed the 2,730 nt NRON and found that it promoted breast cancer cell growth in vitro and in vivo . There are also studies supported our observations that NRON increased tumor cell growth, such as in bladder cancer and gastric Cancer (Xiong et al , 2020; Wang et al , 2021), as well as NRON was highly expressed in esophageal squamous cell carcinomas and inhibited cisplatin‐induced cell apoptosis (Liu et al , 2022).…”
Section: Discussionsupporting
confidence: 81%
“…Various researches have been performed on m6A and ncRNAs to probe the mechanism of malignant phenotype in GC. Wang et al demonstrated that lncRNA NRON facilitated the proliferative capacity in vitro and in vivo via the modulation of ALKBH5 and Nanog (166). It is widely acknowledged that ALKBH5 strictly regulates the m6A methylation of Nanog (167,168).…”
Section: Gastric Cancermentioning
confidence: 99%
“…Then, the m 6 A reader YTHDF2 is involved in the degradation of PTEN , and the half-life of PTEN is increased after YTHDF2 knockdown. The lncRNA lncNRON was recently suggested to exert oncogenic functions in GC by recruiting ALKHB5 to inhibit Nanog mRNA decay [ 104 ]. With regard to miRNAs, miR-338-5p can inhibit the methylation of CDCP1 by suppressing METTL3, which is important because m 6 A modification stimulates CDCP1 translation and accelerates the proliferation and invasion of GC cells [ 105 ].…”
Section: Biological Functions Of M 6 a Rna Modific...mentioning
confidence: 99%